The Impact of Compensation, Work Environment, and Organizational Citizenship Behavior (OCB) on Geothermal Employee Job Satisfaction - Fachrurazi Fachrurazi; Rasty Yulia; Samuel PD Anantadjaya; Irma M Nawangwulan (IAIN Palopo, 2023)
This research is a quantitative study that aims to determine and prove the effect of Compensation, Work Environment, and Organizational Citizenship Behavior (OCB) on Job Satisfaction of geothermal Employees. The sample technique used is probability sampling with a simple random sampling approach using the Slovin formula so that a sample of 93 employees is obtained. Data collection was carried out through distributing questionnaires. The data analysis technique used is the Partial Least Square (PLS) method. The test results obtained in this study (1) compensation has a positive and significant effect on job satisfaction, (2) the work environment has a positive and significant effect on job satisfaction, (3) organizational citizenship behavior (OCB) has a positive and significant effect on job satisfaction. The implications of this research include theoretical and practical, that is, the information in the research is expected to add insight in the development of knowledge in the field of human resource management, as well as have an impact on companies as material for thought and consideration in solving existing problems. The contribution in this study is to assist companies in tackling problems, especially in terms of compensation, work environment, and organizational citizenship behavior (OCB) on employee job satisfaction.